Evaluation of elderly-friendly open space and public service buildings in madiun city using importance performance analysis (IPA) - Eva Anjarika Rahmawati; Rutiana Dwi Wahyunengseh; Asal Wahyuni Erlin Mulyadi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The Age-Friendly City Policy in Madiun City aims to improve the quality of life for the elderly by providing friendly and easy access to open spaces and public buildings. However, challenges in implementation may include appropriate infrastructure management and effective international policies to ensure the availability and availability of services that meet the needs of the city's aging population. This research aims to bridge the perception gap and provide concrete recommendations for improving Madiun's elderly-friendly infrastructure. This research is a development evaluation with a mixed approach (mixed method). The research sample includes various parties, starting from the Madiun City government, which is involved in planning and implementing development for the elderly in Pangongangan Village, the city center, who are users and beneficiaries of these facilities. The data analysis method in this research consists of quantitative and qualitative analysis. Based on the analysis, the majority of the construction of open space facilities and public service buildings in Madiun City is in accordance with development needs, according to the perception of the government and older people. Both parties were satisfied with the development results, especially on items of high essential and performance. However, there needs to be more perception between older people and the government regarding items considered necessary. This shows the need for synchronization between government perceptions and the needs felt by elderly people in developing elderly-friendly infrastructure.